How to Mitigate The Production Risks on Coastal Red Chilli Farming in Kulon Progo Regency - Azmi Basyarahil; Irham Irham; Lestari Rahayu Waluyati (Jurnal Ilmu Pertanian, 2016)
The southern part of the Special Province of Yogyakarta consists of a coastline spanning over 113 km, under the administrations of Bantul, Gunung Kidul and Kulon Progo regencies, that can become an asset and resource of an important economy. Cabe Merah (red chilli) is one of the commodities that show high numbers of productivity in Kulon Progo Regency. Activities of red chilli farming on the coastal land of this regency have been growing, especially since the establishment of commodity auction market to help farmers sell their harvests. The study was conducted to (1) find out the size of production in red chilli agribusiness on coastal land, (2) to analyze the risk levels of production faced by the farmers, and (3) how to mitigate the production risks on coastal red chilli farming. There were 40 participating farmers from Banaran Village, Galur Sub-district, Kulon Progo Regency. The location was intentionally chosen by using  multistage area sampling method. The data used were collected from the production and income of three growing seasons. Data analyses were performed using production risk and The House of Risk methods. Based on the variance coefficient, the production risks level was at 0,03 with the production lower limit of 9.596 Kg/Ha, which showed a low level of risk. The various risk mitigation strategies have been performed by the farmers to lessen the risks that can causes losses in the process of coastal red chilli productions.